The Change in Surgical Case Diversity over the past 15 Years and the Influence on the Pursuit of Surgical Fellowship. Issue 9 (September 2018) - DuCoin, Christopher; Hahn, Alexandra; Baimas-George, Maria; Slakey, Douglas P.; Korndorffer, James R.
The surgical community has expressed concern that residents do not receive the same caliber training as their predecessors and the increase in fellowships have been described as secondary to perceived lack of preparation. Yet, data show no change in total cases even after implementation of the 80-hour workweek. It is hypothesized that the increasing subspecialization of general surgery may decrease in certain resident case numbers. Data were collected from the Accreditation Council for Graduate Medical Education (ACGME) General Surgery Case Logs National Data Report (1999–2014) of mean number of procedures per resident for 19 surgical categories. Statistical analysis was performed with analysis of variance over three time periods between 1999 and 2014. The number of total cases performed by residents has not changed significantly. There was a statistically significant difference observed in the variety of cases: vascular, esophageal, breast, and trauma cases decreased (P < 0.01), whereas major intestinal, hernia, liver, pancreatic, and biliary cases increased (P < 0.01). There are many reasons to pursue additional training after residency. The demonstrated change in case variability, presumably secondary to increasing fellowships, may play a significant role on training and preparation. Close monitoring of curriculums is essential to ensure a comprehensive general surgical education.